Survey of cattle rearing by herdsmen in Lagos State, Nigeria - Asafa, A.R; Okeowo, T.A.; Buraimo, M.A. (Nigerian Journal of Animal Science, 2023)
The incidence of clashes between herders and crop farmers elsewhere necessitated the survey of cattle rearing by herdsmen in Lagos State to obtain baseline information on the herders, their cattle and the commonly grazed forages. Self-administered questionnaires were administered on the herders in Epe, Badagry and Ikorodu Local Government areas being the agrarian zones of Lagos State. Data obtained were analyzed by descriptive statistics. Results on the socio-economic characteristics showed that all the respondents that reared cattle were male and mostly (77%) married. About 70% of respondents have been in the business for over 20 years. 70% of the farmers attended only Quranic school. They mostly (63%) lived with their family who assisted in milk processing. The breeds of cattle reared were White Fulani (50%), Keteku (20%), Sokoto Gudali (20%) and others 10%. The herd size of respondents varied between 11-20 bulls (73%), 16-30 cows (57%) and 20 calves (50%). Most (57%) of the herders grazed their cattle for one to four hours daily. Respondents (67%) also reported incidence of clashes with crop farmers which were settled by the community leaders through restitution. Continuous grazing was mostly (70%) practiced. The commonest forages selected were; Panicum maximum, Chromolaena odorata, Sida acuta, Centrosema pubescens and Tridax procumbens. It is concluded that cattle herders and the residents cohabit in Lagos State.